ChemInform Abstract: Alkali Metal Suboxometalates — Structural Chemistry Between Salts and Metals. Issue 40 (October 2015) - Woersching, Matthias; Hoch, Constantin
Abstract The new cesium‐poor suboxometalates Cs10MO5 (M: Al, Ga, Fe) showing both ionic and metallic bonding are synthesized from mixtures of Cs, M2O3, and Cs2O in the ratio 6:1:7 (Ta crucible, 250—320 °C, 5 h).